Anxiety in Oral Presentations among ESL Student / Nurul Amilin Razawi, Luqmanul Hakim Zulkornain and Razifa Mohd Razlan - Razawi, Nurul Amilin; Zulkornain, Luqmanul Hakim; Mohd Razlan, Razifa (Universiti Teknologi MARA, Negeri Sembilan, 2019)
This study examines the possible causes of anxiety in oral presentations among students who are currently taking English subjects in UiTM Dungun Campus. Communication apprehension especially in doing oral presentations is inevitable among ESL (English as A Second Language) students. This natural phenomenon occurs due to several factors by taking diverse students’ backgrounds into account. However, there are also other factors that may contribute to the students’ anxiety. The respondents were invited to answer a set of questionnaires using Google Forms ™. The questionnaire was adapted and modified from Al-Nouh (2015). A few alterations were made to the questionnaire so as to fit the respondents’ perceptions. From the survey, several factors of anxiety in oral presentations were perceived; language ability, personality traits, preparation and audience interest. Overall, the findings showed that all these four factors did affect the students’ oral presentations. Several implications of the findings were discussed which include setting a friendly and stimulating class environment to cater to the different students’ learning needs, sharing the scoring rubrics for students’ preparation beforehand, encouraging positive attitude among the audience members and emphasizing fluency more than accuracy while using English. It is hoped that the ideas and suggestions discussed will provide the lecturers with basic guidelines of how to improve the students’ command of English language through oral presentation assessments and help the students to work their way out of anxiety.